Еfficacy of probiotics in livestock - Lemishevskyi, V. M. (Baltija, 2023)
The purpose of the study was to investigate on average daily gains, morphometric indicators, ultrastructure, and the content of nucleic acids in the wall of the weaned piglets’ duodenum when feeding with feed containing different amounts of probiotic feed additives Probion-forte and BioPlus 2B. The study was carried out on 28-day-old piglets of the Large White breed. Four groups of 30 piglets each were formed; the control group was fed a standard feed mix, piglets of group I received a standard feed mix with the addition of probiotic feed additive Probion-forte at a dose of 1 g/kg of feed, group II received a feed mix with the addition of Probion-forte at a dose of 0.5 g/kg of feed, and group III received a feed mix with the addition of BioPlus 2B at a dose of 0.4 g/kg of feed for 42 days. The statistical significance of the differences was determined by Student’s t-test, assuming a 5% error rate.
Achievements and research prospects in animal husbandry and veterinary medicine : scientific monograph
Keywords: дванадцятипала кишка поросят; поросята; duodenum of piglets